Educators Communication with Parents in Increasing the Activities and Learning Achievement of Students in Primary Schools - Ujang Efendi; Dian Lestari; Sugiyanto Sugiyanto (Program Studi Magister Manajemen Pendidikan)
Abstract: Educators Communication with Parents in Increasing the Activities and Learning Achievement of Students in Primary Schools. This research aims to describe the communication between educators and parents in increasing the activity and learning achievement of students. The research used is descriptive qualitative case study method. Data collection techniques through interviews, questionnaires, and documentation. The data analysis technique uses steps of data reduction, data presentation, and conclusion (verification). The results showed that 1) communication between educators and parents through official meetings at school, home visits, periodic reports, attitudes of educators to parents and communication outside of school via cell phones, 2) barriers to communication between educators and parents, including busyness of parents, misunderstanding, slow response, difficult signal constraints, lack of focus, distance from home from school, embarrassment and reluctance, and lack of understanding of the content of the conversation, 3) efforts to overcome communication barriers with people parents by changing the schedule of attending school with a partner, home visits, delivering the results of meetings by telephone, and implementing effective communication, 4) there is an impact of communication between educators and parents on the activities and learning achievement of students.Keywords: communicator, educators, parentsDOI: 10.23960/jmmp .v8.i3.2020